2021
DOI: 10.3758/s13428-021-01681-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring naturalistic proximity as a window into caregiver–child interaction patterns

Abstract: The interactions most supportive of positive child development take place in moments of close contact with others. In the earliest years of life, a child's caregivers are the primary partners in these important interactions. Little is known about the patterns of real-life physical interactions between children and their caregivers, in part due to an inability to measure these interactions as they occur in real time. We have developed a wearable, infrastructure-free device (TotTag) used to dynamically and unobt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Specifically, models of proximity that integrate multiple modes of stimulation may be important for characterizing how caregiver-child proximity represents another dimension of children's experiences. Salo et al (2021) documented a small positive association between exposure to adult speech and caregiverchild conversational turns while an adult was in close proximity (<3ft), indicating that while caregiver-involved forms of stimulation or enrichment are related they are far from interchangeable. Given that there may be unique contributions to child functioning of stimulation, characterized as cognitive versus emotional (King et al, 2019), assessing multiple forms of caregiver involvement may allow for better mapping of what aspects of interactions with a caregiver influence specific domains of functioning.…”
Section: Methodological Considerations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, models of proximity that integrate multiple modes of stimulation may be important for characterizing how caregiver-child proximity represents another dimension of children's experiences. Salo et al (2021) documented a small positive association between exposure to adult speech and caregiverchild conversational turns while an adult was in close proximity (<3ft), indicating that while caregiver-involved forms of stimulation or enrichment are related they are far from interchangeable. Given that there may be unique contributions to child functioning of stimulation, characterized as cognitive versus emotional (King et al, 2019), assessing multiple forms of caregiver involvement may allow for better mapping of what aspects of interactions with a caregiver influence specific domains of functioning.…”
Section: Methodological Considerations For Future Researchmentioning
confidence: 99%
“…Methodological challenges to assessing proximity motivated our development of the TotTag (part of the SociTrack system; [Biri et al, 2020]). The TotTag, a small infrastructure-free, wearable device, uses time-of-flight technology to continuously measure physical distance between wearers within cm accuracy (Salo et al, 2021). This tool facilitates our ability to characterize children's physical environments, specifically proximity relationships between children and multiple caregivers in an ecologically valid setting (e.g.…”
Section: Methodological Considerations For Future Researchmentioning
confidence: 99%
“…Regardless of these challenges (or "realistic noise"; Frankenhuis et al, 2019, p. 8), we believe these are invaluable tools in dyadic research. Intensive and naturalistic measures of dyadic interactions that produce time-series data are increasingly being used in tandem with larger longitudinal studies, including mobile eye tracking (Pérez-Edgar et al, 2020), wearable physical proximity (TotTag; Salo et al, 2021), and audio recording devices (LENA; Gilkerson et al, 2017). For instance, King and colleagues (2021) found that six-month infants who experienced inconsistent adult speech and conversational turns across 8-hours of a typical day at home had higher symptoms of psychopathology during toddlerhood, even after accounting for speech quantity and caregivers observed sensitivity.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Although it works as an indirect estimate, the baby's age does not accurately indicate how much a mother has interacted with her infant after birth. The amount of mother-infant interaction might be better captured with devices that track the real-time physical proximity between mothers and infants, which are currently under development ( 56 ). Complementing such quantitative measures with qualitative assessments of mother-infant interactions such as the “still face” and “strange situation” behavioral tasks would further characterize the quality of that maternal investment.…”
Section: Which Are the Mediating Factors?mentioning
confidence: 99%